2020
DOI: 10.1016/j.heliyon.2020.e04860
|View full text |Cite
|
Sign up to set email alerts
|

The first evidence of accumulation and avoidance behavior of macroinvertebrates in a forest soil spiked with human-made iron nanoparticles: A field experiment

Abstract: Both earthworms and terrestrial isopods have been used to evaluate the quality of contaminated soil by NPs. However, most experiments have been conducted in the laboratory and under greenhouse conditions. Besides, little is known of Fe accumulation in earthworms from iron NPs (Fe NPs) under natural conditions. Therefore, the objective of this research was to evaluate the effect of manufactured NPs on the accumulation of Fe in macroinvertebrates from forest soil. Our results revealed that earthworms consume low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(98 reference statements)
0
1
2
Order By: Relevance
“…Their results clearly illustrated the toxicity of a high Fe concentration towards earthworms in natural soil under laboratory conditions. Nevertheless, these findings are not in agreement with that of Hermes et al [209] who carried out similar experiments as Liang et al [207] but under the natural field condition. Their results showed that after 2 hrs of exposure, the Fe contents in soils were similar regardless of the applied iron-based MNP concentrations.…”
Section: The Bioaccumulation and Toxicity Of Mnps To The Soil Ecosystemcontrasting
confidence: 70%
See 1 more Smart Citation
“…Their results clearly illustrated the toxicity of a high Fe concentration towards earthworms in natural soil under laboratory conditions. Nevertheless, these findings are not in agreement with that of Hermes et al [209] who carried out similar experiments as Liang et al [207] but under the natural field condition. Their results showed that after 2 hrs of exposure, the Fe contents in soils were similar regardless of the applied iron-based MNP concentrations.…”
Section: The Bioaccumulation and Toxicity Of Mnps To The Soil Ecosystemcontrasting
confidence: 70%
“…Their results clearly illustrated the toxicity of a high Fe concentration towards earthworms in natural soil under laboratory conditions. Nevertheless, these findings are not in agreement with that of Hermes et al [209] . who carried out similar experiments as Liang et al [207] .…”
Section: Interaction Of Mnps With Soilscontrasting
confidence: 67%
“…The avoidance tests are quick, reasonable, and simple to do as compared to other common sublethal experiments, including reproduction. Nevertheless, the behavioural response is dependent on the species of earthworms tested, the contaminants in which they are exposed, and other soil-speci c variables (Hermes et al, 2020). The harmful effects of ZnO-NPs, according to some studies, are brought on by the release of zinc ions, while other studies asserted that the toxic effects are brought on by the adherence of the particles to the organism's surface or their internalization.…”
Section: Introductionmentioning
confidence: 99%